TRADITIONAL DISHES IN THE FOOD SYSTEM OF AZERBAIJANES - Ismailzade, Piraga Eub oglu (History, Archeology and Ethnography of the Caucasus, 2021)
The article is devoted to the traditional food system of Azerbaijanis. It examines the technology of cooking national dishes, the place of the latter in the daily diet and ritual meals of Azerbaijanis. It is noted that in modern Azerbaijan, some of the rules of traditional food culture, etiquette, in particular when receiving national dishes and drinks, are observed mainly in family life. Today, national dishes are still used in everyday and festive meals. In the Mil-Mugan and Shirvan regions of Azerbaijan, table prayers are read before and after breakfast, lunch and dinner. The rules of etiquette provide special care and attention to the guest, elder, head of the family, children. For lunch and dinner, kebab, kalafur, pilaf, dolma, bozartma, etc. are specially prepared for the guest. The same national dishes were served on the Mavlid Holiday (in honor of the birth of the Prophet Muhammad) in the Mil-Mugan and Shirvan regions of Azerbaijan. The beneficial, healing properties of food are used in traditional medicine. Attention is drawn to the specifics of solemn meals, depending on the purposes of the ceremonies (mourning, wedding (engagement), family celebrations and folk holidays), as well as to the composition of dishes, the subtleties of the technology of their preparation for a large number of people. An extensive assortment of everyday, festive and ceremonial dishes, the degree of perfection of the rules of preparation, the traditional rules of table etiquette confirm the richness of the food culture of Azerbaijanis.
Keywords: Azerbaijan ethnography; table culture; etiquette; national food; supply system; material culture; hospitality.